Síntese em batelada ou fluxo contínuo de compostos N- e O-heterocíclicos e avaliação da atividade inibitória frente a enzima acetilcolinesterase - Monteiro, Júlia Lammoglia (2017)
Alzheimer’s disease (AD) is currently the most common type of dementia, characterized by a progressive loss of memory and deterioration of cognitive functions. Most approved drugs for AD treatment are acetylcholinesterase (AChE) inhibitors (AChEI), mainly responsible for reduced rates of the neurotransmitter acetylcholine (ACh) in the synaptic process. In this context, organic synthesis, specially the synthesis of heterocycle compounds, plays a key role in drug discovery, since these compounds are related to a broad spectrum of biological activity. In the last decades, the use of continuous flow reactors in organic synthesis stands out as an important tool for developing safer, more efficient and sustainable methodologies. This thesis is focused on the synthesis of coumarins, hydantoins, indoles and pyrroles derivatives, aiming to obtaining potential AChE inhibitors. When possible, the synthesis of such compounds was conducted employing alternative methodologies based on green chemistry concepts, aiming to decrease the synthetic steps, use alternative energy sources, e.g. microwave reactors, substitute toxic solvents or even apply solvent-free protocols, and use continuous flow reactors. Initially, a new method was developed for the one-pot synthesis of high structural complexity piperidinocoumarins in good yields and selectivities, trough asymmetric organocatalysis followed by an Ugi-Smiles type reaction. One alternative route was also employed for the synthesis of reduced hydantoins over tree steps, starting from asymmetric aziridines. Also regarding the hydantoin’s synthesis, it was developed a continuous flow protocol of the Bucherer-Bergs reaction to afford 5- and 5,5-disubstituted hydantoins faster, safer, and more efficient when compared to the conventional methodology. Finally, we developed a protocol for the trifluoromethylation of indoles and pyroles under continuous flow conditions, based on the Minisci reaction, using perfluor halides as starting material. Aiming to collaborate with the structureactivity studies of the coumarins against AChE, hydantoin-coumarin hybrids were synthesized. All compounds were evaluated against AChE and showed low to moderate enzymatic activity.